South Africa : 2010 Article IV Consultation-Staff Report; Staff Supplement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for South Africa. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
The global financial crisis had a much more pronounced impact on South Africa relative to some other large emerging markets. The overriding economic policy challenge is to reduce unemployment and inequality through higher economic growth. Unemployment is a key policy focus; and a wage subsidy aimed at younger unskilled workers, as well as other policy options, are under discussion. IMF staff broadly concur with the authorities' approach, and believe that the current fiscal plan strikes the right balance between supporting the recovery through sustained infrastructure investment while ensuring fiscal sustainability.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet